2017
DOI: 10.1186/s12890-017-0510-7
|View full text |Cite
|
Sign up to set email alerts
|

Visceral and subcutaneous abdominal adiposity and pulmonary function in 30-year-old adults: a cross-sectional analysis nested in a birth cohort

Abstract: BackgroundSeveral studies have verified body fat distribution in association with pulmonary function (PF), mainly waist circumference, but few have used measures able to distinguish abdominal fat compartments. The present study aims to verify the association of visceral adipose tissue (VAT) and subcutaneous adipose tissue (SAT) with PF measures.MethodsIn 1982, all hospital births occurring in Pelotas, Brazil, were identified and those livebirths have been followed. In 2012–13, the cohort participants were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The effects of obesity on pulmonary function are more associated with FVC than with FEV 1 [37]. Furthermore, VFA is positively correlated with intra-abdominal visceral fat volume [38], with numerous studies examining the relationship between FVC and FEV 1 (VFA, FVC, and FEV 1 showed negative correlations) [25,[39][40][41]. Values are the median and the 25 th and 75 th percentiles.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of obesity on pulmonary function are more associated with FVC than with FEV 1 [37]. Furthermore, VFA is positively correlated with intra-abdominal visceral fat volume [38], with numerous studies examining the relationship between FVC and FEV 1 (VFA, FVC, and FEV 1 showed negative correlations) [25,[39][40][41]. Values are the median and the 25 th and 75 th percentiles.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, intrathoracic fat volumes positively correlated with visceral abdominal fat volumes (26) and were inversely associated with lung function (27,28). Although the impact of increases in intrathoracic fat is less known, considering its anatomical proximity to the lung, intrathoracic fat could have a more significant effect on lung function as compared with pericardial fat.…”
Section: Discussionmentioning
confidence: 99%
“…As well as a meta-analysis of the association between WC and lung function were proven (18). Visceral adipose tissue is inversely associated with FEV1 (Forced Expiratory Volume in one second) and FVC (Forced Vital Capacity) in both genders (19). Fat-Free Mass (FFM) also shows a positive relationship with pulmonary function (20).…”
Section: Introductionmentioning
confidence: 95%